2020
DOI: 10.3390/ijms21249434
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Spatial Fibrin Growth and Impaired Contraction of Blood Clots in Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease associated with thrombotic complications. To elucidate pathogenic mechanisms, hemostatic disorders in RA were correlated with other laboratory and clinical manifestations. Hemostasis was assessed using relatively new complementary tests, the spatial growth of a plasma clot (Thrombodynamics assay), and contraction of whole blood clots. Platelet functionality was assessed with flow cytometry that quantified the expression of P-selectin and the fibrinogen-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Question 5: How can the apparent contradiction between impaired clot contraction in patients with thrombotic diseases and the predominance of compressed RBCs indicating clot contraction in thrombi be resolved? There is now evidence that clot contraction is diminished in patients with many (pro)thrombotic conditions: ischemic stroke, 5 venous thromboembolism, 6 systemic lupus erythematosus, 8 sickle cell disease, 38 high risk of pregnancy loss, 9 rheumatoid arthritis, 10 postoperative thrombosis, 12 hyperhomocysteinemia, 11 and COVID-19. 39 At the same time, quantitative determination of the composition of venous and arterial thrombi and pulmonary emboli has revealed that these structures contain few biconcave RBCs, and they are almost entirely polyhedrocytes or intermediate forms of RBCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Question 5: How can the apparent contradiction between impaired clot contraction in patients with thrombotic diseases and the predominance of compressed RBCs indicating clot contraction in thrombi be resolved? There is now evidence that clot contraction is diminished in patients with many (pro)thrombotic conditions: ischemic stroke, 5 venous thromboembolism, 6 systemic lupus erythematosus, 8 sickle cell disease, 38 high risk of pregnancy loss, 9 rheumatoid arthritis, 10 postoperative thrombosis, 12 hyperhomocysteinemia, 11 and COVID-19. 39 At the same time, quantitative determination of the composition of venous and arterial thrombi and pulmonary emboli has revealed that these structures contain few biconcave RBCs, and they are almost entirely polyhedrocytes or intermediate forms of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of blood clots is followed by their volumetric shrinkage known as contraction or retraction 1,2 driven by forces generated by the platelet cytoskeleton that are transmitted to fibrin fibers 3 . The contraction of blood clots and thrombi can occur not only in vitro, but also in vivo as a pathophysiologic process that improves hemostasis 4 , increases blood flow past otherwise obstructive thrombi 5 , prevents thrombotic embolization 6 , and alters clot susceptibility to fibrinolysis 7 , and other clinical implications 5,6,[8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The impaired platelet contractility as a potential prothrombotic mechanism is less apparent, although the inability of platelets to cause full clot contraction has been observed earlier in a number of (pro)thrombotic states of various origins [32,[55][56][57]. The reduced ability of blood clots and thrombi to shrink can promote thrombosis via several pathogenic mechanisms that include increased obstructiveness of thrombi [56][57][58][59], reduced susceptibility to fibrinolysis [60], and increased embologenicity or reduced resistance to rupture [56,61]. Therefore, the secondary platelet dysfunction following platelet activation is a novel hemostatic mechanism in SLE and probably in other autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular scale, increasing evidences suggest that platelets can undergo mechanosensing upon receiving these hemodynamic stimuli. Key players in such mechanosensing processes include von Willebrand factors (VWF) ( Savage et al, 1996 ; Fu et al, 2017 ), fibrinogen ( Butera and Hogg, 2020 ; Peshkova et al, 2020 ), mechanoreceptors including glycoprotein Ib (GPIb) ( Chen et al, 2016 ; Ju et al, 2016 ) and glycoprotein IIb/IIIa (GPIIb/IIIa or integrin α IIb β 3 ) ( Nesbitt et al, 2009 ; Chen Y et al, 2019 ), and mechanosensitive ion channels ( Abbonante et al, 2017 ; Ilkan et al, 2017 ; Liu et al, 2021 ). Further, activated platelets generate contractile forces to stabilize and consolidate the thrombus ( Osdoit and Rosa, 2001 ; Ono et al, 2008 ; Hansen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%